Quizizz application training as an alternative to learning assessment - Ernawati; Shinta Wahjusaputri; Hari Setiadi; Firmansyah; Rini Yaumi Habibah; Syarifah, Nur (JURNAL ABDIMAS SERAWAI, 2023)
ABSTRACT In this new normal era, academics, especially teachers, are required to continue to look for various learning media so that the learning process can continue both face-to-face at school or online. Teachers are also continuously required to develop competencies both in the personal, social, and professional pedagogical realms. Of the four main competencies, there are two core competencies related to the use of technology and information. To develop these abilities, teachers feel the need to study the latest learning media so they can continue to innovate in the learning and assessing process. Competency development in the use of this technology is one of the problems experienced by SDT Pelita Hati. Therefore, to assist teachers in increasing competence in the use of information technology at SDT Pelita, the UHAMKA Community Partnership Program will conduct online assessment media training. Current learning media used during the learning and assessment process can use gamification-based learning media. One of the popular gamification-based learning media is the Quizizz application. Related to this application, PKM SPS UHAMKA held an activity with the topic "Quiziz Application Training as an Alternative Learning Assessment". This activity produces outputs in the form of articles on online media and video publications via YouTube. This activity provides benefits in the form of new knowledge for the participants. According to the participants, the Quizizz application is easy to practice, can increase student enthusiasm, as well as an exciting and fun atmosphere. ABSTRAK Di era kenormalan baru ini, sivitas akademika khususnya guru dituntut untuk terus mencari berbagai media pembelajaran agar proses belajar dapat terus dilakukan baik tatap muka disekolah ataupun secara daring. Guru juga terus dituntut mengembangkan kompetensi baik itu diranah pedagogik kepribadian, sosial, dan profesional. Dari keempat kompetensi utama tersebut, terdapat dua kompetensi inti terkait dengan pemanfaatan teknologi dan informasi. Untuk mengembangakan kemampuan tersebut, guru-guru dirasa perlu untuk mempelajari media pembelajaran terkini agar dapat terus berinovasi dalam proses belajar maupun menilai. Pengembangan kompentensi dalam pemanfaatan teknologi ini menjadi salah satu persoalan yang dialami oleh SDT Pelita Hati. Oleh sebab itu, untuk membantu guru dalam peningkatkan kompetensi pemanfaatan teknologi informasi di SDT Pelita, Program Kemitraan Masyarakat UHAMKA akan mengadakan pelatihan media asesmen daring. Media pembelajaran kekinian yang digunakan selama proses pembelajaran maupun penilaian dapat menggunakan media pembelajaran berbasis gamifikasi. Salah satu media pembelajaran berbasis gamifikasi yang cukup populer adalah aplikasi Quizizz. Terkait dengan aplikasi tersebut, PKM SPS UHAMKA mengadakan kegiatan dengan topik “Pelatihan Aplikasi Quizizz Sebagai Alternatif Asesmen Pembelajaran”. Kegiatan ini menghasilkan luaran berupa artikel pada media daring dan publikasi video melalui youtube. Adapun kegiatan ini memberikan manfaat berupa pengetahuan baru bagi para pesertanya. Menurut para peserta, aplikasi Quizizz mudah dipraktikkan, dapat meningkatkan antusiasme siswa, serta suasana yang seru dan menyenangkan